Association between blood–urea–nitrogen-to-albumin ratio and in-hospital mortality in patients diagnosed with coronavirus disease 2019: a retrospective cohort study - Ruoqing Zhou; Dianzhu Pan (European Journal of Medical Research)
Abstract Background The blood–urea–nitrogen-to-albumin ratio (BAR) is recognized as a novel prognostic indicator; however, there is a limited number of studies investigating the relationship between BAR and in-hospital mortality associated with coronavirus disease 2019 (COVID-19). Therefore, the present investigation aims to explore the correlation between BAR and in-hospital mortality in patients with COVID-19 in China. Methods This retrospective observational study enrolled a cohort of 1027 patients diagnosed with COVID-19 between December 2022 and March 2023. Multivariate Cox regression analyses were used to ascertain the independent association between BAR and in-hospital mortality among patients with COVID-19. Furthermore, stratified analyses were used to investigate potential interaction effects with variables, such as age, sex, COVID-19 Severity, hypertension, coronary artery disease, and diabetes mellitus. Results A total of 117 patients (11.4%) died from various causes during hospitalization. Subsequent to adjustment for confounding variables, patients in the highest BAR tertile exhibited an elevated risk for in-hospital mortality relative to those in the lowest tertile (hazard ratio [HR] 2.44 [95% confidence interval CI 1.24–4.79]) when BAR was treated as a categorical variable. When considering BAR as a continuous variable, a 6% increase in the prevalence of in-hospital mortality was observed for each 1-unit increase in BAR (adjusted HR 1.06 [95% CI 1.03–1.08]; P < 0.001). Stratified analyses revealed a consistent association between BAR and in-hospital mortality due to COVID-19. Conclusions BAR exhibited a significant relationship with in-hospital mortality in patients with COVID-19, suggesting that a higher BAR is associated with a poorer prognosis. However, further research is required to confirm these findings.